Early Chinese Manuscript Collections Sayings, Memory, Verse, and Knowledge - Krijgsman, Rens (Brill, 2023)
As the first study of manuscript collections, this book asks what changes when sayings, stories, songs, and spells are brought together on the same carrier. Covering a plethora of manuscripts from the Warring States and early empires, and spanning sources from philosophy, historiography, poetry, and technical literature, this study describes the whole life-cycle of multiple texts collected on a single manuscript. Drawing on comparative and interdisciplinary advances and based on careful study of manuscript materiality and textuality, this book shows the importance of collections in the development of and access to text and knowledge in early China.